A minority view on the majority: A personal meeting summary on the explosion mechanism of supernovae. Issue Volume 12:Issue S331(2017) (17th October 2017) - Soker, Noam
Abstract: I present my minority view that the majority (or even all) of core collapse supernovae (CCSNe) are driven by jets rather than by neutrinos, and that the majority of type Ia supernovae (SN Ia) reach their explosion via the core degenerate scenario. New simulations presented at the meeting did not achieve an explosion of CCSNe. I critically examine other arguments that where presented in support of the neutrino-driven model, and present counter arguments that support the jet-driven explosion mechanism. The jets operate via a negative jet feedback mechanism (JFM). The negative feedback mechanism explains the explosion energy being several times the binding energy of the core in most CCSNe. We do not know yet what mechanism explodes massive stars and we do not know yet what evolutionary route leads white dwarfs to explode as SN Ia, and so we must be open to different ideas and critically examine old notions.